Analysis the Influence of Sling Direction on Pad Eye Strength - Ardianti, Andi; Hamzah; Sitepu, Ganding; Mahendra Amir, Ihza (International Journal of Metacentre, 2022)
One of the stages of ship production using the grand block system is the erection process, where in this process the blocks weighing up to million Tons will be lifted. This study aims to see whether the sling angle used in the block lifting process will produce different stresses, strains, and deformations in the pad eye. Sling angle variations used in this study are 45°, 60°, 75° and 90° with a tensile load of 55 tons or 539365.75 N. This research was conducted using the finite element method and assisted by ANSYS software. Based on the results of the analysis, the maximum X-axis normal stress is 57.85 MPa which occurs at a sling angle of 45°, the maximum Y-axis normal stress is 143.32 MPa which occurs at a 90° sling angle, the maximum XY shear stress is 51.712 MPa which occurs at a sling angle of 45° and a Von-Mises stress of 151.47 MPa which occurs at a sling angle of 90°. As for the shear strain XY, the maximum strain that occurs at an angle of 45° is 6.4 x and for the maximum Von-Mises strain occurs at an angle of 90° by7.4 x . And the maximum total deformation value is obtained by7,286 x mm that occurs at a sling angle of 45°.For each variation of the sling angle used, the strength of the pad eye still meets the classification requirements because the resulting value is still below the permissible value. The difference in the results obtained after using variations in the angle of the sling shows that the difference in the direction of the pull of the sling has a different effect on the strength of the Pad eye.